1999
DOI: 10.1021/jp9840230
|View full text |Cite
|
Sign up to set email alerts
|

Impeded Rotation of a Protein in a Sol−Gel Matrix

Abstract: The sol-gel encapsulation process has been exploited in recent years for the immobilization of proteins to be used as biosensors. Sol-gels derived from tetramethyl orthosilicate provide a stable environment for the macromolecule combined with the free flow of small substrates to a protein's binding site. The functionality of a number of enzymes within the solid matrix has been demonstrated. However, very little biophysical characterization of the encapsulated proteins has been done. In this study, time-resolve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
1
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(83 citation statements)
references
References 23 publications
(49 reference statements)
3
77
1
2
Order By: Relevance
“…Actually, the discrepancy should only be a factor 2, as for most other proteins (see Table 1 and Fig. 1); a more accurate experimental value, determined by fluorescence depolarization (45), is D R expt ϭ 15 s Ϫ1 (at 20°C). As discussed above, most of this factor-2 discrepancy should be attributed not to hydration but to the fact that myoglobin is not a compact sphere.…”
Section: Discussionmentioning
confidence: 99%
“…Actually, the discrepancy should only be a factor 2, as for most other proteins (see Table 1 and Fig. 1); a more accurate experimental value, determined by fluorescence depolarization (45), is D R expt ϭ 15 s Ϫ1 (at 20°C). As discussed above, most of this factor-2 discrepancy should be attributed not to hydration but to the fact that myoglobin is not a compact sphere.…”
Section: Discussionmentioning
confidence: 99%
“…The mobilities of glass entrapped proteins have been characterized by fluorescence anisotropy [26,[59][60][61][62], tryptophan phosphorescence [63], and photobleaching experiments [62]. In addition to apoMb, enhanced conformational stability at elevated temperatures has been observed for many glass-entrapped proteins including α-lactalbumin [22], lysozyme [22,24], human serum albumin [24,26,54], creatine kinase [31], monellin [59], oncomodulin [64], cytochrome c [65], and carbonic anhydrase [66].…”
Section: Discussionmentioning
confidence: 99%
“…3,[23][24][25][26][27][28] Fluorescence anisotropy studies have demonstrated that proteins in sol-gel pores experience dramatically hindered rates of rotation due to protein adsorption to the pore walls. 23,29,30 Alternatively, the pore dimensions could influence the protein structural stability by affecting the dynamics of the surrounding solvent, which is intimately coupled to the dynamics of the protein. Water in nanoscopic environments (i.e.…”
Section: Introductionmentioning
confidence: 99%